36. Evaluation of a Best Practice Alert (BPA) to Improve Pneumocystis jirovecii Prophylaxis Prescribing in Cancer Patients Receiving High-dose Corticosteroids in an Outpatient Setting. (4th December 2021) - Ross, Justine Abella; Tegtmeier, Bernard; Johnson, Deron; Nanayakkara, Deepa; Puing, Alfredo; Ho, Stephanie; Taplitz, Randy; Dadwal, Sanjeet; Dickter, Jana
Abstract: Background: In patients (pts) with cancer, the risk of Pneumocystis jirovecii pneumonia (PJP) is a function of dose and duration of corticosteroids (CS), underlying immunodeficiency, and immunosuppressive drugs. Trimethoprim/sulfamethoxazole (TMP/SMX) and atovaquone (ATO) are effective prophylaxis (ppx) agents against PJP. Guidelines recommend PJP ppx for pts on > 20 mg /day of prednisone or its equivalent for ≥ 1 month. A best practice alert (BPA) to identify pts receiving CS may assist with improving PJP ppx prescribing in cancer pts. Methods: PJP BPA was created to identify pts on CS (excluding hydrocortisone) with no active prescription for TMP/SMX or ATO ppx in EMR. Dapsone and pentamidine excluded since not preferred agents at our institution. PJP case: positive PJP polymerase chain reaction (PCR) from bronchoalveolar lavage (BAL) > 84 copies or positive PJP direct fluorescent antibody (DFA) or cytology with clinical and radiographic suspicion. PJP PCR from BAL < 84 copies/ml with negative DFA and cytology excluded. Preventable PJP (P-PJP): pts after CS > = 30 days without PJP ppx. Non-preventable PJP (NP-PJP) : pts after CS < 30 consecutive days, or on PJP ppx (non-compliance, failure), or day +1 to +30 post hematopoietic cell transplant (HCT). Pre-intervention (pre-i) PJP pts 3/1/2018 to 7/31/19 (17 months), post-intervention (post-i) PJP pts 8/1/19 to 2/1/20 (18 months) evaluated to assess BPA impact on PJP inpatient (inpt) admissions. Results: In the post-i, the BPA fired 3, 588 times in 1, 302 pts. Pre-i: 20 P-PJP, 13 NP-PJP out of 33 pts. Post-i: 6 P-PJP, 25 NP-PJP out of 31 pts. The BPA fired in 4/31 PJP pts in the post-i period: 2/6 of P-PJP, 2/25 NP-PJP. The number of P-PJP decreased from 20 to 6 in the post-i period (p=0.0097). Conclusion: Implementation of a decision support tool significantly decreased the number of P-PJP. The BPA was limited by identifying pts after CS were prescribed after the initial visit leading to periods of CS use without ppx and inability to calculate CS dosing and length of prescription. BPA provided passive education in the outpatient setting and future opportunities include refining the EMR to better identify pts at risk for developing PJP. Disclosures: All Authors : No reported disclosures